Odpowiedź:
zad 1
6x + 7 = 5x – 10
6x - 5x = - 10 - 7
x = -17
18 – 8x = 5x + 23
- 8x -5x = 23 -18
- 13x = 5 /: -13
x = [tex]-\frac{5}{13}[/tex]
100 x + 24 = 23 + 90 x
100x - 90x = 23 - 24
10x = -1 / :10
x = - 0,1
4 x – 10 = 32 x + 10
4x -32x = 10 + 10
-28x = 20 / :-28
x = [tex]-\frac{20}{28}[/tex]
x = [tex]-\frac{5}{7}[/tex]
zad 2
4x – 5 – 3x = 5x +7 – 2
x - 5 = 5x + 5
x - 5x = 5+5
-4x = 10 /:-4
x = -2,5
23 x +12 – 8 – 21x = 14 + 3x - 12
2x + 4 = 2 +3x
2x - 3x = 2 - 4
-x = -2 / :-1
x = 2
Daj naj proszeeeeeee